The Incidence and Characteristic of Acute Kidney Injury as A Complication of Severe Burn Injury in Patients Receiving Fluid Resuscitation - Biben, Johannes Albert (Lingkar Studi Bedah Plastik Foundation, 2013)
Background: Acute kidney injury is important factor that can increase mortality in patient with severe burn injury. Knowledge about incidence and characteristic of acute kidney injury among severe burned patients will help medical practitioner to establish appropriate medical decision and health care protocol. Method: PubMed, Cochrane Library, and GoogleTM search yielded 12 articles. The articles were screened by inclusion criteria, exclusion criteria, and full text reading. Five remaining articles appraised in regard of validity, importance, and applicability. Result: Incidence of acute kidney injury among severely burned patients varies from 24.4% to 53.3%. According to the study with best level of evidence, a systematic review, the incidence of AKI is 28.8% (95% CI 26.8%-30.7%). AKI can occur early or late, and may progress. Progressive AKI has highest mortality rate. Conclusion: AKI is common complication among patients with severe burn injury. Approximately one- third to half of patients with severe burn injury will develop AKI in the course of the disease. Early clinical assessment and re-evaluation are important in severe burn injury management.